(untitled) - Horsfield, Brenda (London, 1972)
This book stes out to describe the rise of a new big science the exploitation of which will certainly cause man-kind as much excitement, foreboding, danger, worry and stimulation as have space and atomic energy in their turn, and there is still no clear idea of what the ultimate cost will be.
Keywords: Hải dương học,Oceanography